Photodynamic composite film with double antibacterial activities as well as preparation and application of photodynamic composite film
By introducing ε-polylysine (PL) into photodynamic inactivation (PDI) technology, the outer structure of Gram-negative bacteria is destroyed and ROS penetration is promoted, and the problem of insufficient antibacterial activity of PDI technology on Gram-negative bacteria is solved, which significantly enhances the antibacterial effect and extends the shelf life of food.
Patent Information
- Application Number
- CN202411994070.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing photodynamic inactivation (PDI) technology has insufficient antibacterial activity against Gram-negative bacteria in food packaging, mainly due to its poor permeability to ROS and limited ROS diffusion distance.
By introducing a stable food-grade cationic polymer ε-polylysine (PL), as a "forward team", it destroys the outer structure of Gram-negative bacteria, promotes reactive oxygen species (ROS) penetration, and combines efficient photosensitizer preparation methods to significantly enhance the photodynamic inactivation (PDI) effect.
The antibacterial activity of photodynamic inactivation (PDI) technology against Gram-negative bacteria in food packaging can effectively reduce the number of bacteria by 6 logarithmic units after 15 minutes of light and extend the shelf life of fresh pork to 10 days.
Smart Images

Figure CN119775609A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the fields of nanotechnology and material science, and specifically relates to a photodynamic composite film with dual antibacterial activity and the preparation and application thereof. Background Art
[0002] Food waste is a global problem, among which microbial spoilage is one of the main causes of food loss. In order to meet this challenge, the development of effective antimicrobial packaging materials has become a research hotspot. Although traditional packaging based on chemical antimicrobial agents has a certain effect, the migration process of the antimicrobial agents limits its application. Therefore, it is particularly important to find green and efficient antimicrobial materials.
[0003] Photodynamic inactivation (PDI) technology, as an emerging antibacterial method, has attracted much attention due to its broad-spectrum and highly effective antibacterial properties. This technology uses photosensitizers to generate reactive oxygen species (ROS) under light, thereby rapidly inactivating microorganisms. Natural photosensitizers are particularly suitable for food-related applications due to their natural origin and low toxicity. However, many natural photosensitizers suffer from aggregation-induced quenching (ACQ), which significantly inhibits the generation of reactive oxygen species, limiting their effectiveness in practical applications. Berberine, a natural isoquinoline alkaloid derived from Coptis chinensis, has long been widely used to treat bacterial infections. Berberine exhibits aggregation-induced emission (AIE) phenomenon under visible light irradiation, rather than aggregation quenching (ACQ), which enables it to still emit fluorescence and generate a large amount of reactive oxygen species in the aggregated state, thereby enhancing the antibacterial effect. The applicant previously utilized the interaction between the AIE properties of berberine and 3,4,5-methoxycinnamic acid (3,4,5-TCA) to successfully prepare photodynamically inactivated nanoparticles (BTNPs), which exhibited significantly increased ROS production and enhanced antibacterial effects under visible light activation.
[0004] Photodynamic inactivation (PDI) technology has indeed achieved remarkable results in bacterial inactivation, especially showing great potential in improving the sensitivity of drug-resistant bacteria to antibiotics. However, PDI's antibacterial activity against Gram-negative bacteria (such as Escherichia coli) in food packaging is indeed insufficient. The outer membrane of Gram-negative bacteria is composed of lipoproteins, phospholipids, and lipopolysaccharides, forming a dense barrier that can block the penetration of many antibiotics and ROS. It has poor permeability to ROS, which makes it difficult for ROS to directly contact microorganisms and effectively inactivate them; in addition, the limited diffusion distance and short lifespan of ROS also increase the difficulty of inactivating Gram-negative bacteria. Summary of the invention
[0005] In view of the technical difficulty that the existing photodynamic inactivation (PDI) technology has insufficient antibacterial activity against Gram-negative bacteria in food packaging, the present invention aims to provide a photodynamic composite film with dual antibacterial activity and its preparation and application, by introducing a stable food-grade cationic polymer ε-polylysine (PL) as a "vanguard" to destroy the outer structure of Gram-negative bacteria, promote the penetration of reactive oxygen species (ROS), and significantly enhance the photodynamic inactivation (PDI) effect.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: The present invention provides a method for preparing a photodynamic composite film with dual antibacterial activity, comprising: Dialdehyde nanocellulose and gelatin are mixed, stirred in a water bath, and glycerol is added to obtain a mixed solution; photodynamic inactivated nanoparticles and ε-polylysine are mixed and stirred, then added to the mixed solution, stirred at room temperature, and dried to obtain a photodynamic composite film with dual antibacterial activity.
[0007] The volume ratio of the dialdehyde nanocellulose to gelatin is 1:10-20, and the water bath conditions are: 50° C.-70° C., stirring for 20 min-40 min.
[0008] Furthermore, the volume ratio of the dialdehyde nanocellulose to gelatin is 1:15, and the water bath temperature is 60°C.
[0009] The added amount of glycerol is 10% to 30% of the gelatin mass.
[0010] Furthermore, the added amount of glycerol is 20% of the mass of gelatin.
[0011] The mass ratio of the photodynamic inactivation nanoparticles to ε-polylysine is 4:25-50, and the mixture is stirred at room temperature for 10 min-30 min.
[0012] Furthermore, the mass ratio of the photodynamic inactivation nanoparticles to ε-polylysine is 4:25.
[0013] The photodynamic inactivation nanoparticles are obtained by the following steps: mixing a berberine solution with a 3,4,5-TCA solution, adjusting the pH value, adding a preheated PBS solution, stirring in the dark, ultrasonically treating, dialyzing, and freeze-drying to obtain the photodynamic inactivation nanoparticles.
[0014] The volume ratio of the berberine solution to the 3,4,5-TCA solution is 1:1-2, the solution is preheated to 50-70° C. and stirred for 10 min-20 min, and the dialysis molecular weight cutoff is 3.5 kDa.
[0015] Furthermore, the volume ratio of the berberine solution to the 3,4,5-TCA solution is 1:1.
[0016] The dialdehyde nanocellulose is obtained by oxidizing cellulose nanocrystals with sodium periodate, the mass ratio of sodium iodate to cellulose nanocrystals is 1:2, and the oxidation condition is stirring at room temperature in the dark for 30 minutes.
[0017] The present invention provides a photodynamic composite film with dual antibacterial activity obtained by the above-mentioned preparation method.
[0018] The photodynamic composite film has dual antibacterial activity and aggregation-induced luminescence performance.
[0019] The application of the above-mentioned photodynamic composite film with dual antibacterial activity in the preservation of fresh meat products.
[0020] The photodynamic composite film can inhibit the growth of microorganisms, protein oxidation, and lipid oxidation in fresh meat products, thereby extending the shelf life.
[0021] Compared with the prior art, the beneficial effects of the present invention are: The present invention provides a method for preparing a photodynamic composite film with dual antibacterial activity, which combines the advantages of photodynamic therapy and antibacterial agents, and provides a new method for preparing a composite film with high-efficiency antibacterial properties. By introducing ε-polylysine (PL) as the "vanguard" and combining the preparation method of an efficient photosensitizer, the antibacterial activity of the photodynamic inactivation (PDI) technology against Gram-negative bacteria in food packaging is significantly enhanced, providing a new idea and method for solving the existing technical problems; by preparing photodynamic inactivation nanoparticles and dialdehyde nanocellulose, and mixing them with gelatin, glycerol, etc., a photodynamic composite film with dual antibacterial activity is finally obtained; natural photosensitizer nanoparticles are used as the core of photodynamic therapy, and ε-polylysine (PL) is introduced as an antibacterial enhancer. The two materials are incorporated into a matrix composed of gelatin and dialdehyde nanocellulose (CNC) to form a composite film.
[0022] Furthermore, through the chemical reaction of berberine and 3,4,5-TCA, nanoparticles with photodynamic inactivation properties are generated. These nanoparticles can produce reactive oxygen species (ROS) under light, thereby killing or inhibiting the growth of microorganisms; cellulose nanocrystals are oxidized by sodium periodate to generate nanocellulose with dialdehyde functional groups. These dialdehyde functional groups can undergo cross-linking reactions with polymers such as gelatin to improve the mechanical properties and chemical stability of the composite film; The photodynamic composite film with dual antibacterial activity provided by the present invention innovatively proposes a photodynamic composite film with dual antibacterial activity, which has both aggregation-induced emission (AIE) characteristics and dual antibacterial activity, takes natural photosensitizer nanoparticles as the core of photodynamic therapy, and introduces food-grade cationic polymer ε-polylysine (PL) as a vanguard. By utilizing its cationic properties, it can effectively destroy the outer structure of Gram-negative bacteria, making bacteria more vulnerable to ROS attack. ROS can penetrate deeper into the bacteria and destroy their biomacromolecules, such as nucleic acids, proteins and lipids, thereby enhancing the photodynamic inactivation effect; the combination of PL and photodynamic inactivation nanoparticles provides an additional antibacterial layer for the composite film, enhances the killing ability of microorganisms, and significantly improves The photodynamic inactivation (PDI) efficiency was improved, and the number of bacteria could be effectively reduced by 6 logarithmic units after 15 minutes of illumination. The composite film also had excellent UV shielding performance, high transparency (over 86.57%), good hydrophobicity and enhanced mechanical strength. In view of the poor permeability of the outer membrane of Gram-negative bacteria to ROS, the composite film improved the contact efficiency and inactivation effect of ROS by optimizing the composition and structure, thereby effectively combating this type of bacteria and overcoming the problem of poor permeability of ROS to Gram-negative bacteria. It achieved the goal of green and efficient antibacterial, provided strong support for reducing food waste, and could effectively inhibit the microbial growth, protein oxidation, lipid oxidation and pH changes of pork samples, successfully extending the shelf life of fresh pork at 4°C to 10 days.
[0023] The application provided by the present invention is a green and efficient synergistic antibacterial strategy based on photodynamic therapy (PDT), which not only provides new ideas and methods for the field of food preservation, but also demonstrates the great potential of the dual antibacterial composite film based on PDT technology in pork preservation; the composite film performs well in inhibiting the growth of microorganisms, protein oxidation, lipid oxidation and pH changes in pork samples, and successfully extends the shelf life of fresh pork at 4°C to 10 days; this composite film not only has strong antibacterial ability, but also has good physical and chemical properties, which makes it have broad application prospects in food packaging, cold chain logistics and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 TEM images, histograms of particle size distribution, and ROS generation assays of BT NPs of the present invention, wherein A is a TEM image, B is a histogram of particle size distribution, and C is a ROS generation assay; Figure 2 The infrared spectra of the composite film and raw materials of the present invention, wherein A is the infrared spectra of the raw material aldehyde nanocellulose, and B is the infrared spectra of the composite of different raw materials; Figure 3The light transmittance and fluorescence spectrum of the composite film of the present invention are shown in Figure 1, wherein A is the light transmittance of the composite film, and B is the fluorescence spectrum of the composite film; Figure 4 is the water contact angle (WCA) value of the composite film of the present invention; Figure 5 The antibacterial activity photos of the composite film of the present invention, and the antibacterial activity graphs against Escherichia coli and Staphylococcus aureus, wherein A is the antibacterial activity photo of the composite film with or without light irradiation, B is the antibacterial activity against Escherichia coli, and C is the antibacterial activity against Staphylococcus aureus; Figure 6 GD and GD / BT of the present invention 2 -PL film packaged pork samples during storage test results of TPC value, pH value, TVB-N and TBARS value, where A is the GD and GD / BT under light-proof or light-proof conditions. 2 -TPC value of pork samples packaged with PL film during storage, B is the change of pH value during the test period, C is the change of TVB-N value during the test period, and D is the change of TBARS value during the test period. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0026] The present invention is described in further detail below: Example 1 This embodiment provides a photodynamic composite film with dual antibacterial activity, which specifically includes the following steps: 1. Preparation of Photodynamic Inactivation Nanoparticles (BT NPs) The methanol solution of berberine (concentration 0.02 mmol / mL) and the DMSO solution of 3,4,5-TCA (concentration 0.02 mmol / mL) were mixed in a volume ratio of 1:1, and the pH value of the solution was adjusted to 7.0; the mixed solution was added to phosphate buffer solution (PBS) preheated to 60°C, stirred for 15 min in the dark, and ultrasonically treated at room temperature for 1 h; the ultrasonically treated solution was dialyzed in deionized water for 12 h (molecular weight cutoff value was 3.5 kDa), and freeze-dried to obtain BT NPs.
[0027] 2. Preparation of dialdehyde nanocellulose (DAC) 1 g of cellulose nanocrystals (McLean Co., Ltd., Shanghai, China) were oxidized with 0.5 g of sodium periodate to obtain dialdehyde nanocellulose (DAC), and the concentration of the oxidized solution was adjusted to 2 wt %.
[0028] 3. Preparation of photodynamic composite films with dual antibacterial activity (1) Mix 15 mL of gelatin (GE) (2 wt%) and 1 mL of DAC (2 wt%) in a ratio of 15:1 (v / v) and stir in a 60°C water bath for 30 min to obtain a mixed solution. Add glycerol (0.06 g) accounting for 20% of the mass of GE to the mixed solution to obtain a GD solution.
[0029] (2) Mix 5.76 mg of BT NPs with 36 mg of ε-polylysine (PL) and stir for 20 min to obtain a mixture of BT NPs and PL; add the mixture of BT NPs and PL into 18 mL of GD solution; after stirring evenly at room temperature, pour it into a polyethylene culture dish with a diameter of 9 cm and dry it naturally at room temperature to obtain a photodynamic composite film with dual antibacterial activity.
[0030] (3) Carefully peel off the dried photodynamic composite film from the culture dish, seal it and store it at room temperature for later use.
[0031] Example 2 This embodiment provides a photodynamic composite film with dual antibacterial activity, which specifically includes the following steps: 1. Preparation of Photodynamic Inactivation Nanoparticles (BT NPs) The methanol solution of berberine (concentration 0.02 mmol / mL) and the DMSO solution of 3,4,5-TCA (concentration 0.02 mmol / mL) were mixed in a volume ratio of 1:2, and the pH value of the solution was adjusted to 7.0; the mixed solution was added to phosphate buffer solution (PBS) preheated to 50°C, stirred for 15 min in the dark, and ultrasonically treated at room temperature for 1 h; the ultrasonically treated solution was dialyzed in deionized water for 12 h (molecular weight cutoff value was 3.5 kDa), and freeze-dried to obtain BT NPs.
[0032] 2. Preparation of dialdehyde nanocellulose (DAC) 1 g of cellulose nanocrystals (McLean Co., Ltd., Shanghai, China) were oxidized with 0.5 g of sodium periodate to obtain dialdehyde nanocellulose (DAC), and the concentration of the oxidized solution was adjusted to 2 wt %.
[0033] 3. Preparation of photodynamic composite films with dual antibacterial activity (1) Mix 10 mL of gelatin (GE) (2 wt%) and 1 mL of DAC (2 wt%) in a ratio of 15:1 (v / v) and stir in a 50°C water bath for 20 min to obtain a mixed solution. Add glycerol (0.02 g) (10% of the mass of GE) to the mixed solution to obtain a GD solution.
[0034] (2) Mix 5.76 mg of BT NPs with 72 mg of ε-polylysine (PL) and stir for 20 min to obtain a mixture of BT NPs and PL; add the mixture of BT NPs and PL into 18 mL of GD solution; after stirring evenly at room temperature, pour it into a polyethylene culture dish with a diameter of 9 cm and dry it naturally at room temperature to obtain a photodynamic composite film with dual antibacterial activity.
[0035] (3) Carefully peel off the dried photodynamic composite film from the culture dish, seal it and store it at room temperature for later use.
[0036] Example 3 This embodiment provides a photodynamic composite film with dual antibacterial activity, which specifically includes the following steps: 1. Preparation of Photodynamic Inactivation Nanoparticles (BT NPs) The methanol solution of berberine (concentration 0.02 mmol / mL) and the DMSO solution of 3,4,5-TCA (concentration 0.02 mmol / mL) were mixed in a volume ratio of 1:1, and the pH value of the solution was adjusted to 7.0; the mixed solution was added to phosphate buffer solution (PBS) preheated to 70°C, stirred for 20 min in the dark, and ultrasonically treated at room temperature for 1 h; the ultrasonically treated solution was dialyzed in deionized water for 12 h (molecular weight cutoff value was 3.5 kDa), and freeze-dried to obtain BT NPs.
[0037] 2. Preparation of dialdehyde nanocellulose (DAC) 1 g of cellulose nanocrystals (McLean Co., Ltd., Shanghai, China) were oxidized with 0.5 g of sodium periodate to obtain dialdehyde nanocellulose (DAC), and the concentration of the oxidized solution was adjusted to 2 wt %.
[0038] 3. Preparation of photodynamic composite films with dual antibacterial activity (1) Mix 20 mL of gelatin (GE) (2 wt%) and 1 mL of DAC (2 wt%) in a ratio of 15:1 (v / v) and stir in a 50°C water bath for 20 min to obtain a mixed solution. Add glycerol (0.09 g) (30% by weight of GE) to the mixed solution to obtain a GD solution.
[0039] (2) Mix 5.76 mg of BT NPs with 36 mg of ε-polylysine (PL) and stir for 20 min to obtain a mixture of BT NPs and PL; add the mixture of BT NPs and PL into 18 mL of GD solution; after stirring evenly at room temperature, pour it into a polyethylene culture dish with a diameter of 9 cm and dry it naturally at room temperature to obtain a photodynamic composite film with dual antibacterial activity.
[0040] (3) Carefully peel off the dried photodynamic composite film from the culture dish, seal it and store it at room temperature for later use.
[0041] Example 4 In this example, based on Example 1, the performance of the photodynamic composite film with dual antibacterial activity obtained in Example 1 was tested, and the performance of the composite films prepared with different addition amounts of BT NPs+PL and the composite films prepared with only BT NPs added but no PL was tested. The specific composition of the composite films is shown in Table 1.
[0042] Table 1: Composition of composite films
[0043] (1) Structural characterization Characterization and analysis: Transmission electron microscopy (TEM, model: JEM-2800, Japan) and field emission scanning electron microscopy (FESEM, model: Nava NanoSEM 450, Czech Republic) were used to observe the morphological characteristics of berberine, 3,4,5-TCA and BT NPs; attenuated total reflection Fourier transform infrared (ATR-FTIR) method (Bruker INVENNIO, Germany) was used.
[0044] Quantification of ROS generation: 2',7'-dichlorodihydrofluorescein diacetate (DCFH-DA) was used as a fluorescent probe to quantitatively analyze the generation of reactive oxygen species induced by BT NPs.
[0045] The UV–visible spectrophotometer (UV300, 190–1100 nm, China) was used for the measurements with air as the background; the fluorescence intensity of the composite films in the wavelength range of 450–700 nm (λex = 405 nm) was determined using a fluorescence spectrophotometer (FL8500, Korea).
[0046] (2) Mechanical properties The texture of the film was analyzed using a texture analyzer (TA.XT Plus, UK) at room temperature. 2 ) with a 48 h equilibration period at 75% relative humidity.
[0047] (3) Water vapor permeability (WVP) and water contact angle (WCA) The WVP value is determined gravimetrically. The sample centrifuge nozzle unit area A (m 2 ) and weight gain per unit time.
[0048] The WCA of the prepared composite films was measured using an OCA20 optical analyzer (Dataphysics OCA20 DCAT21, Germany).
[0049] (4) Thermogravimetric analysis (TGA) The thermal stability of the prepared composite films was evaluated using a TGA instrument (Q-600 / Q1000, USA).
[0050] Antibacterial activity: The activated Staphylococcus aureus and Escherichia coli solutions were resuspended in sterile PBS. Subsequently, 20 μL of bacterial suspension (10 7 -10 8 CFU / mL) were evenly distributed on the sample membrane. The illumination group was irradiated with a xenon lamp (long arc xenon lamp, 400-800 nm, 300 W), and the control group was maintained in a dark environment. After 15 minutes of exposure to light, the sample membrane was transferred to 10 mL PBS and vortexed for 2 minutes to elute the bacteria. Finally, 100 μL of the eluate was inoculated on LB nutrient agar, and after incubation at 37°C for 16 hours, the surviving microorganisms were counted and recorded. The experiment was performed in triplicate, and the data obtained were expressed as the mean and standard deviation.
[0051] Figure 1 TEM images, histograms of particle size distribution, and ROS generation assay of BT NPs.
[0052] By the attached Figure 1 The data show that BT NPs present a good self-assembled structure; through image measurement, the average size of BT NPs is 14 nm; by analyzing the histogram, it can be concluded that the size of BT NPs is relatively uniform and mainly distributed around 14 nm; under light conditions, the amount of ROS generated by BT NPs is about three times that of berberine alone, which indicates that BT NPs have excellent photodynamic antibacterial effects; the increase in ROS generation is attributed to the restriction of intramolecular motion in self-assembled photosensitive nanoparticles, which improves the efficiency of fluorescence emission and ROS generation.
[0053] Figure 2 Infrared spectra reveal the molecular interactions between the components in the composite films.
[0054] By the attached Figure 2The data show that in the dialdehyde nanocellulose (CNC) sample, the pyranose ring skeleton vibration (COC) and OH vibration appear at 1145 cm⁻¹ and 1643 cm⁻¹, respectively. The positions of the characteristic peaks confirm the presence of pyranose ring skeleton vibration and OH vibration in the CNC sample; After DAC and GE were mixed, the aldehyde group in DAC reacted with the amino group in GE to form a Schiff base reaction. After the reaction, the infrared spectrum showed a peak at 1631 cm -1 ~1544 cm -1 A new C=N stretching vibration band appeared in the range of 1000–1000 cm-1. An absorption band at 1035 cm-1 was observed, which was attributed to the hydroxyl group in glycerol. The addition of antimicrobial agents did not significantly change the structure of the film, and similar characteristic peaks were present in all samples. -1 A broad peak appears at 3292 cm, which is related to the hydrogen bond vibration in the composite film. The addition of nanoparticles and PL causes the broad peak to red-shift to 3292 cm -1 , indicating that hydrogen bonding is enhanced; the position of the characteristic peaks confirms the presence of pyranose ring skeleton vibration and OH vibration in the CNC sample; the appearance of the aldehyde absorption peak indicates that DAC has been successfully oxidized; the appearance of the C=N stretching vibration band verifies that the aldehyde group in DAC reacts with the amino group in GE by a Schiff base reaction; 1035 cm -1 The absorption band at 40° confirmed the presence of glycerol; the addition of antimicrobial agents did not change the film structure, indicating that the film had good stability; the red shift of the broad peak indicated that the addition of nanoparticles and PL enhanced the hydrogen bonds in the composite film, further verifying the phenomenon of enhanced hydrogen bonds.
[0055] Figure 3 The transmittance and fluorescence spectra of all composite films.
[0056] By the attached Figure 3The data show that the pure GE film exhibits a slight UV shielding ability, but the UV transmittance is still high, indicating that its UV protection effect is limited; the GD film has a strong UV absorption ability due to the Schiff base group formed, which significantly reduces the UV transmittance, so the UV transmittance of the GD film is significantly reduced, showing a strong UV shielding effect; the GD / BT and GD / BT-PL composite films have the lowest UV transmittance in the UVA and UVB regions because the benzene ring and carbonyl group in BT NPs can effectively absorb ultraviolet rays, showing excellent UV protection performance; through fluorescence emission spectroscopy, it was found that all composite films showed high transmittance in the visible light region (more than 86.57%), indicating that the antibacterial agent is uniformly dispersed in the film matrix and does not affect the transparency of the film; the intrinsic fluorescence intensity of the composite film increases with the increase of BT NPs content, confirming that the composite film has strong AIE activity; the incorporation of PL has no significant effect on the AIE activity of the film, indicating that PL mainly plays other roles (such as enhancing mechanical properties, improving processability, etc.) without affecting the AIE performance.
[0057] In summary, the GD / BT-PL film has excellent transparency, which ensures the visual appeal of the packaging material while not affecting consumers' intuitive observation of the food in the package; it has strong UV shielding ability, which effectively prevents UV oxidative damage to food and extends the shelf life of food; it also exhibits good AIE performance, providing new ideas for the future development of packaging materials with special optical effects.
[0058] WCA (contact angle) is often used to evaluate the hydrophilicity and hydrophobicity of the surface of GD-based films. Food packaging films need to have a certain degree of hydrophobicity to ensure the best preservation effect. The test results are shown in the attached Figure 4 shown.
[0059] By the attached Figure 4 The data show that all films show significant hydrophobicity. Compared with the contact angle of pure gelatin film (57.2°), the hydrophobicity of GD film is stronger, which is mainly attributed to the occurrence of Schiff base reaction. This reaction changes the hydrophilic groups (such as amino and aldehyde groups), thereby enhancing the hydrophobicity of the film. The contact angle of GD film is 90.32°. After adding BT1 and BT2, the contact angle fluctuates, but the GD / BT 2 The contact angle of the film (93.96±1.46) is higher than that of the GD film. After adding PL, the contact angle of the GD / PL film increases to 92.6°, which is higher than that of the GD film but lower than that of the GD / BT film. 2 The contact angle of GD / BT-PL film (91.82±0.55) is slightly lower than that of GD / PL film, but still higher than that of GD film and GD / BT film. 2The contact angle of the -PL film was the highest, 95.58±2.78, and it was the most hydrophobic of all the films. This result showed that the addition of PL to the GD-based film enhanced the strength of the hydrogen bond interaction with the gelatin molecules, promoted the rearrangement of the film's molecular structure, reduced the exposure of the hydrophilic groups, and thus formed a denser surface structure, especially after the addition of PL and BT. 2 The composite film exhibits excellent hydrophobicity and is suitable for food packaging to ensure optimal preservation effect.
[0060] The antibacterial activity of the composite film, as well as the antibacterial activity against Escherichia coli and Staphylococcus aureus, are shown in the attached Figure 5 shown.
[0061] By the attached Figure 5 The data show that under sunlight, GD / BT-PL film exhibits significant synergistic antibacterial effects. Whether in light or dark environments, GD / BT-PL film can continuously release antibacterial agents and effectively inactivate bacteria, indicating that GD / BT-PL film provides excellent antibacterial properties for food packaging films. Analysis of antibacterial mechanism: As the "leading force" in the system, cationic PL can actively attach to the negatively charged bacterial membrane. This attachment causes the bacterial cell membrane to form holes and rupture, thereby destroying the integrity of the bacteria; ROS, as the "subsequent force", has high permeability and can quickly penetrate bacterial cells. ROS effectively inactivates bacterial cells through oxidative stress, further enhancing the antibacterial effect; there is a synergistic effect between low concentrations of BTNPs and PL, and this synergistic effect significantly enhances the antibacterial activity of GD / BT-PL film against Gram-negative bacteria (such as Escherichia coli).
[0062] In summary, the synergistic effect of low concentrations of BT NPs and PL can significantly enhance the antibacterial activity against Gram-negative bacteria, providing excellent antibacterial properties for food packaging films.
[0063] Example 5 Based on Examples 1 to 4, this Example conducts a meat product preservation application test on the photodynamic composite film with dual antibacterial activity prepared in Example 1 of the present invention and the control film in Example 4 to examine the effects of different films on the performance of fresh meat products.
[0064] Determination of the freshness preservation ability of pork: Fresh pork tenderloin purchased from a local farmer's market was transferred to a laboratory equipped with an ice-cold cooler and then cut into pieces (2.5 × 2 × 0.5 cm, about 2 g) immediately after removing the outer layer on a clean bench. Pork samples were respectively treated with GD, GD / BT 2 -PL or PE film (control) wrapping. Half of GD and GD / BT 2-PL samples were treated with light, while the other half were protected from light. All samples were placed in plastic trays and stored in a refrigerator at 4°C for 10 days. The total colony count (TPC), volatile basic nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS), and pH of pork samples were determined on days 1, 4, 7, and 10.
[0065] The total bacterial colony count (TPC) in pork samples was assessed using the plate count method.
[0066] The pH of pork samples wrapped in different films was measured using the method described by Ibeogu et al. (2024) (Li J, Zhang X, Lv J, et al. Fabrication and characterization of blue honeysuckle anthocyanins-loaded nanocomposite films and the application in pork preservation [J]. Food Hydrocolloids, 2024, 149.): each pork sample was added to 20 mL of distilled water and homogenized at 10,000 rpm for 1 minute; the pH of the resulting filtrate was determined using a pH meter calibrated with commercially available buffer solutions (pH 4.00, 7.00, and 9.00) to ensure accuracy, and each sample was measured 3 times.
[0067] According to the national food safety standard (GB5009.228-2016), the TVB-N value of pork was determined by the Kjeldahl method using a fully automatic Kjeldahl nitrogen analyzer (Buqi K375, Switzerland).
[0068] Malondialdehyde (MDA) is combined with thiobarbituric acid (TBA), and the OD values at 532 nm and 600 nm are measured using a spectrophotometer to calculate the TBA value. First, the sample is processed according to the instructions of the kit (MDA detection kit, Shanghai Zhuocai Company), and the absorbance at 532 nm and 600 nm is quantitatively measured, named A532 and A600, respectively. The MDA content is calculated according to the instructions of the kit. The specific results are shown in the attached Figure 6 shown.
[0069] By the attached Figure 6 The data show that under light conditions, the total nitrogen content of the GD / BT²-PL composite film group is higher than that of the GD film group and the control group; under dark conditions, the total nitrogen content of the GD / BT²-PL composite film group is higher than that of the GD film group and the control group. 2 The total nitrogen content of the -PL composite film group was also higher than that of the GD film group and lower than that of the GD / BT group under light conditions. 2-PL composite film group, the total nitrogen content of the control group remained relatively stable or slightly decreased during the entire experimental period; GD / BT 2 -PL composite films showed better performance under light conditions, with higher total nitrogen content, and light conditions had an impact on GD / BT 2 -PL has a positive impact on the performance of composite films, proving that GD / BT 2 -PL composite film effectively inhibited the microbial growth and pH value of fresh pork during storage and prevented lipid oxidation (low TBARS value) through synergistic antimicrobial action, thus effectively extending the shelf life of pork.
[0070] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A method for preparing a photodynamic composite film with dual antibacterial activity, characterized in that: include: The dialdehyde nanocellulose and gelatin are mixed, stirred in a water bath, and glycerol is added to obtain a mixed solution; The photodynamic inactivated nanoparticles were mixed with ε-polylysine and stirred, and then added into the mixed solution, stirred at room temperature, and dried to obtain a photodynamic composite film with dual antibacterial activity.
2. The method for preparing the photodynamic composite film with dual antibacterial activity according to claim 1, characterized in that: The volume ratio of the dialdehyde nanocellulose to gelatin is 1:10-20, and the water bath conditions are: 50° C.-70° C., stirring for 20 min-40 min.
3. The method for preparing the photodynamic composite film with dual antibacterial activity according to claim 1, characterized in that: The added amount of glycerol is 10% to 30% of the gelatin mass.
4. The method for preparing the photodynamic composite film with dual antibacterial activity according to claim 1, characterized in that: The mass ratio of the photodynamic inactivation nanoparticles to ε-polylysine is 4:25-50, and the mixture is stirred at room temperature for 10-30 min.
5. The method for preparing the photodynamic composite film with dual antibacterial activity according to claim 1, characterized in that: The photodynamic inactivation nanoparticles are obtained by the following steps: mixing a berberine solution with a 3,4,5-TCA solution, adjusting the pH value, adding a preheated PBS solution, stirring in the dark, ultrasonically treating, dialyzing, and freeze-drying to obtain the photodynamic inactivation nanoparticles.
6. The method for preparing the photodynamic composite film with dual antibacterial activity according to claim 5, characterized in that: The volume ratio of the berberine solution to the 3,4,5-TCA solution is 1:1-2, the solution is preheated to 50°C-70°C and stirred for 10 min-20 min, and the dialysis molecular weight cutoff is 3.5 kDa.
7. The method for preparing the photodynamic composite film with dual antibacterial activity according to claim 1, characterized in that: The dialdehyde nanocellulose is obtained by oxidizing cellulose nanocrystals with sodium periodate, the mass ratio of sodium iodate to cellulose nanocrystals is 1:2, and the oxidation condition is stirring at room temperature in the dark for 30 minutes.
8. A photodynamic composite film with dual antibacterial activity obtained by the preparation method according to any one of claims 1 to 7.
9. The photodynamic composite film with dual antibacterial activity according to claim 8, characterized in that: The photodynamic composite film has dual antibacterial activity and aggregation-induced luminescence performance.
10. Use of the photodynamic composite film with dual antibacterial activity according to any one of claims 8 to 9 in preserving fresh meat products.
Citation Information
Patent Citations
Degradable nano preservative film with photodynamic bactericidal activity and preparation method thereof
CN115850807A
Epsilon-polylysine and curcumin combined mediated photodynamic sterilization method and application
CN117379574A
Multifunctional hydrogel integrating photo-thermal characteristics and photo-thermal responsiveness as well as preparation method and application of multifunctional hydrogel
CN118307728A
Biologically compatible, biofilm disrupting composition and methods
US20240325335A1